2004
DOI: 10.1107/s0108270104025776
|View full text |Cite
|
Sign up to set email alerts
|

Poly[methylammonium tris(μ2-formato-κ2O:O′)cobalt(II)]

Abstract: The structure of the title compound, {(CH(6)N)[Co(CHO(2))(3)]}(n), consists of a three-dimensional net of central Co(II) ions connected via formate (methanediolate) bridges. The negative charge is compensated by protonated methylamine cations. The CoO(6) chromophores form slightly distorted octahedra, which are bridged by C atoms of formate groups. The central Co atom lies on an inversion center and most of the other atoms lie on an m plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…However the coexistence of phases in the powder samples at low temperature (see below), points to aw eak first-order character.T his behaviour is not commonf or formate complexes presenting an order-disorder phase transition. [11] Although the crystal structureo fc omplex 1A has been described in previous papers, [9,10] the structural phase transition hasn ot been reported before. Both structures can be depicted as a3 Da nionic [Co(HCOO) 3 ] À framework with a4 12 6 3cpu perovskite-liket opology (in Schläflin otation).…”
Section: Crystal Structurementioning
confidence: 96%
See 2 more Smart Citations
“…However the coexistence of phases in the powder samples at low temperature (see below), points to aw eak first-order character.T his behaviour is not commonf or formate complexes presenting an order-disorder phase transition. [11] Although the crystal structureo fc omplex 1A has been described in previous papers, [9,10] the structural phase transition hasn ot been reported before. Both structures can be depicted as a3 Da nionic [Co(HCOO) 3 ] À framework with a4 12 6 3cpu perovskite-liket opology (in Schläflin otation).…”
Section: Crystal Structurementioning
confidence: 96%
“…At RT,t he hydrogens connected to the carbon atoms are disordered in (15)8,i ndicating that the possible rotationo ft he hydrogen atoms from the CH 3 unit disappears, although the ellip-soids of theseh ydrogen atoms remain bigger than those of the NH 3 unit (see Figure 3). Once the lowt emperature phase is achieved (1B), the mirror plane is lost, andt hen there are six crystallographically independenth ydrogen atoms [H (6), H (9) and H(5) in the CH 3 -u nit and H(1), H(2) and H(8) in the NH 3 -]. All these variationsi mply slightly changes in the distances of the hydrogen bond network where the methylammonium molecule is involved (see Ta ble2and Figure 3).…”
Section: Crystal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In this work we focus on a family of hybrid perovskites of formula [CH 3 NH 3 ][M(HCOO) 3 ]. The compounds with M = Mg 2+ , Mn 2+ , Fe 2+ , Co 2+ , Cu 2+ , Zn 2+ and Cd 2+ have been previously described 16,[30][31][32] and it has been shown that this family displays anomalous thermal expansion behaviour. 16 Regarding the magnetic properties, the Mn 2+ compound has been described as a weak ferromagnet below 7.8 K with a spin-flop transition at 0.45 T. 32 We have recently reported magnetic ordering-induced multiferroic behaviour in the Co 2+ compound together with a remarkable anisotropic magnetic and electric behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Being isostructural with [Co(CHO 2 ) 3 ] n .nCH 6 N (Boča, et al, 2004), complex (I) consists of a three-dimensional network of Zn II ions connected via formate (methanediolate) bridges. As depicted in Fig.…”
Section: Commentmentioning
confidence: 99%